Design of band‐notched ultra wideband antenna for indoor and wearable wireless communications. Issue 3 (1st February 2015) - Ur‐Rehman, Masood; Abbasi, Qammer Hussain; Akram, Muhammad; Parini, Clive
Abstract : Design of a tapered‐slot ultra wideband (UWB) band‐notched wearable antenna is presented in this study. The antenna operation covers the whole UWB frequency spectrum of 7.5 GHz ranging from 3.1 to 10.6 GHz, while rejecting the wireless local area network operation at 5.25 GHz band. The performance of the antenna is analysed through simulations and validated through measurements. The antenna makes use of ultra‐thin liquid crystal polymer (LCP) substrate. The presented return loss and radiation pattern results show that the antenna offers excellent performance in the UWB frequency band in free space. Use of the LCP substrate makes the antenna to efficiently mitigate the bending effects. Moreover, the antenna performs well in on‐body configurations and its working is little affected in adversely hot and humid weather conditions. Furthermore, it offers good on‐body communication link and pulse fidelity. These features make the proposed antenna design a well‐suited choice for hand‐held and wearable UWB applications.